The correlation of the low birth weight with stunting incident on child aged 6-59 months in Lampung-Indonesia - Yesi Nurmalasari; Ringgo Alfarisi; Syawalia Kartika (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Stunting or short was failed condition to grow of the baby (0-11 months old) and toodler (12-59 months old) impacted of the cronic malnutrition especially in the first 1.000 days of life its effecting the children to be too short. LBW is a factor that most dominant risk against stunting on child.Purpose : This research was to know the Correlation between history of low body weight of birth with the genesis stunting of the toodler aged 6-59 months in Mataram Ilir Village Seputih Surabaya Central Lampung 2019.Methods: This type of research is analysis observation with cross sectional design with purposive sampling as the sampling technique and Chi Square test as the bivariate analysis.Results: The results of the analysis showed that the frequency distribution of children with a history of LBW was 85 (35%), and the proportion of respondents with a history of normal weight birth was 152 (64.1%). While the frequency of the incidence of infants with normal height was 141 (59.5%), and the frequency of genesis stunting was 96 (40.5%). The results showed that the p-value was 0.005 and OR was 2.282 (95% CI: 1.29 - 3.8).Conclusion: There was a significant relationship between history of LBW and genesis stunting.